A novel stabilisation scheme for hybrid photovoltaic, fuel-cell and diesel gen-set utilisation system. (1st March 2012) - Sharaf, Adel M.; Aktaibi, Adel A.
The paper presents a novel FACTS-based modulated filter compensator scheme for a hybrid renewable photovoltaic – diesel – fuel cell common DC bus interface scheme. The proposed standalone photovoltaic-diesel-fuel system is fully interfaced using the common AC-DC collection bus topology. This allows for full decoupling of AC and DC type green source and ensures full flexibility in controlling the interface-power electronic devices. The hybrid scheme utilises a novel FACTS-based modulated filter-capacitor compensator device to ensure full stabilisation of the DC common bus to ensure minimal inrush current transients and voltage swings under sudden source excursions and load disturbances. The novel dynamic error driven variable structure-sliding mode controller for the FACTS-modulated filter compensator as well as conventional PI-controller for dynamic efficient utilisation of the back-up diesel gen-set ensure the objectives of a safe decoupled interface with maximum green energy utilisation and enhanced power quality of the hybrid renewable energy scheme.